Antarctic Tardigrada - Utsugi,Kazuo; Ohyama,Yoshikuni (National Institute of Polar Research, 1989)
P(論文) For studying the Antarctic tardigrades, a variety of 31 samples including mosses, lichens and algae were examined. These samples were supplied by the staff of the National Institute of Polar Research in Japan, having been collected mostly at several stations close to Japanese Syowa Station in Antarctica. Tardigrades sorted out were mounted in Gum-chloral for phase-contrast microscope observation. Five species were found in 15 samples collected from 7 stations. Hypsibius arcticus was widely found in all of the samples from 5 stations (Ongul Island, Langhovde, Skarvsnes, Einstoingen and Rundvagshetta). The other 4 species were rarely found; Macrobiotus harmsworthi from Rundvagshetta and Einstoingen, Diphascon chilenensis from Einstoingen and the S0r Rondane Mountains, D. ongulensis from Langhovde, and Pseudechiniscus sp. from Strandnibba. Of these tardigrades, P. sp. was reported from Antarctica probably for the first time. departmental bulletin paper